2019
DOI: 10.1002/cne.24826
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory corticospinal tract axons sprout within the cervical cord following a dorsal root/dorsal column spinal injury in the rat

Abstract: The corticospinal tract (CST) is the major descending pathway controlling voluntary hand function in primates, and though less dominant, it mediates voluntary paw movements in rats. As with primates, the CST in rats originates from multiple (albeit fewer) cortical sites, and functionally different motor and somatosensory subcomponents terminate in different regions of the spinal gray matter. We recently reported in monkeys that following a combined cervical dorsal root/dorsal column lesion (DRL/DCL), both moto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…After SCI, recovery or compensatory reaching and grasping is mediated by several spared systems that respond after injury. Sparing and sprouting of the CST and RST are two of the most well-characterized mechanisms involved in regaining reaching and grasping following SCI that are conserved across species [75][76][77][78][79]. In addition, plasticity of primary afferent fibers is also a key contributor to improved function post-injury.…”
Section: Neural Plasticity Associated With Reaching and Grasping After Scimentioning
confidence: 99%
“…After SCI, recovery or compensatory reaching and grasping is mediated by several spared systems that respond after injury. Sparing and sprouting of the CST and RST are two of the most well-characterized mechanisms involved in regaining reaching and grasping following SCI that are conserved across species [75][76][77][78][79]. In addition, plasticity of primary afferent fibers is also a key contributor to improved function post-injury.…”
Section: Neural Plasticity Associated With Reaching and Grasping After Scimentioning
confidence: 99%
“…They also hint at the potential of plasticity within the remaining pathways, since all the animals were able to recover quadrupedal locomotion. Moreover, recent studies showed extensive somatosensory and motor corticospinal sprouting following an incomplete SCI [ 50 52 ]. The recovery potential will depend on the ability of remaining neuronal circuitry to generate new and coordinated activity through neuroplasticity and could lead to compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lesions to the dorsal column have led to deficits in some or all of the above functions. For example, an incision to the dorsal column at the C1 region in rats produced deficits with object handling in rats, though they quickly learned to compensate with alternate limb or body movements (McKenna & Whishaw, 1999) and may be attributed to corticospinal and somatosensory sprouting (Fisher et al, 2018; McCann et al, 2020). In addition, myelopathy in these two fasciculi owing to a rare complication of intrathecal chemotherapy has been shown to produce lower limb numbness and a pronounced lack of proprioception in the same region (Joseph & Reyes, 2014).…”
Section: General Description Of Human Spinal Cord Anatomymentioning
confidence: 99%